Seven myths of the Spanish conquest - Restall, Matthew, 1964- (Oxford University Press, 2003)
Here is an intriguing exploration of the ways in which the history of the Spanish Conquest has been misread and passed down to become popular knowledge of these events. The book offers a fresh account of the activities of the best-known conquistadors and explorers, including Columbus, Cortes, and Pizarro. Using a wide array of sources, historian Matthew Restall highlights seven key myths, uncovering the source of the inaccuracies and exploding the fallacies and misconceptions behind each myth. This vividly written and authoritative book shows, for instance, that native Americans did not take the conquistadors for gods and that small numbers of vastly outnumbered Spaniards did not bring down great empires with stunning rapidity. We discover that Columbus was correctly seen in his lifetime-and for decades after-as a briefly fortunate but unexceptional participant in efforts involving many southern Europeans. It was only much later that Columbus was portrayed as a great man who fought against the ignorance of his age to discover the new world.; Restall also shows that the Spanish Conquest relied heavily on black and native allies, who provided many thousands of fighters, vastly outnumbering the conquistadors. In fact, the native perception of the Conquest differed sharply from the Spanish version-they saw it as a native civil war in which the Spaniards played an important but secondary role. The Conquest, Restall shows, was more complex-and more fascinating-than conventional histories have portrayed it. Seven Myths of the Spanish Conquest offers a richer and more nuanced account of a key event in the history of the Americas.